Review of the state of art of DX-SAHP systems to obtain domestic hot water - Quitiaquez, William; Simbaña, Isaac; Isaza-Roldán, César A.; Quitiaquez, Patricio; Nieto-Londoño, César; Toapanta-Ramos, Fernando (Enfoque UTE, 2020)
The investigation purpose is to elaborate a detailed review about previous published investigations with direct-expansion solar-assisted heat pumps (DX-SAHP) used for water heating, in the last years. The growing energy consumption, the using of refrigerants that weaken the ozone layer, the greenhouse gases emission to the atmosphere and the global warming effect are the main problems that the conventional water heating systems present. Using hydrocarbons as refrigerants represents a pollution reduction and it is also the best option to replace hydrochlorofluorocarbons and chlorofluorocarbons, due to their low values of global warming potential and ozone depletion potential, close to 0. A DX-SAHP system takes advantage of the thermal solar energy directly by using a bare flat-plate solar collector. These systems provide domestic hot water over 50 °C and heating water volumes until 200 liters reaching COP values higher than 4. Solar energy and the using of alternative refrigerants with a low environmental impact are proposed to reach this purpose.